TO NUDGE OR NOT TO NUDGE IN MASTERY GOAL DRIVEN EDUCATION: THAT IS THE QUESTION? - Lana Ashby (PUPIL: International Journal of Teaching, Education and Learning, 2026)
Almost two decades ago, Thaler and Sustein (2008) explored what is well known as ‘nudge’ theory. Think about the strategic placement of the pasta on one side of the supermarket aisle and the tomato sauce on the other. The supermarket does not provide directional signage to purchase the items together, but the gentle nudge and ease of access ensures that they are more likely to be purchased simultaneously. Though initially developed in the field of behavioural science, the use of nudges in legal education (or more broadly in higher education) to enhance student engagement is yet to be fully explored. Arguably, the theory could be used at any level of learning. Rejecting the notion that nudging diminishes student autonomy (Hausman & Welch, 2010) or undermines psychological barriers for independent decision making (Bovens, 2009), there is a danger that students may experience ‘nudge’ overload or misinterpret a nudge, as a result of their academic orientation, whether mastery or performance (Graham, Toon, Wynn-Williams and Beatson, 2017). Therefore, this paper seeks to explore how experimental, experiential and innovative nudges have been incorporated into the writer’s teaching practice, encouraging further student engagement and skill mastery. Using a mastery goal orientation, this paper/presentation then explores an experiential and arguably successful application of nudges which may be linked to the improved performance across the higher-grade boundaries and a failure rate of less than 1% in classes of 250+ students. These include highly effective use of email, innovative use of podcasts, gamification of learning, the self-styled “preparation pods” and experimental, adaptive revision lectures (including flipped learning). Teaching should be grounded in liberation and development rather than authority and control. The usefulness of these combined approaches was highlighted in student evaluations. I have been exploring the use of nudges over the past fourteen years of teaching and have found that the innovative use of a range of experimental nudges in legal education may have a positive direct impact on student engagement, which should result in increased skill mastery.